Tuning electro-optic susceptibity via strain engineering in artificial PZT multilayer films for high-performance broadband modulator - Zhu, Minmin (2017)
A series of Pb(Zr1-xTix)O3 multilayer films alternatively stacked by Pb(Zr0.52Ti0.48)O3 and Pb(Zr0.35Ti0.65)O3 layers have been deposited on corning glass by magnetron sputtering. The films demonstrate pure perovskite structure and good crystallinity. A large tetragonality (c/a) of ∼1.061 and a shift of ∼0.08 eV for optical bandgap were investigated at layer engineered films. In addition, these samples exhibited a wild tunable electro-optic behavior from tens to ∼250.2 pm/V, as well as fast switching time of down to a few microseconds. The giant EO coefficient was attribute the strain-polarization coupling effect and also comparable to that of epitaxial (001) single crystal PZT thin films. The combination of high transparency, large EO effect, fast switching time, and huge phase transition temperature in PZT-based thin films show the potential on electro-optics from laser to information telecommunication.